2022
DOI: 10.3390/v14030559
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the MMTV Zoonotic Hypothesis to Account for Geographic Variation in Breast Cancer Incidence

Abstract: Human breast cancer incidence varies by geographic location. More than 20 years ago, we proposed that zoonotic transmission of the mouse mammary tumor virus (MMTV) from the western European house mouse, Mus musculus domesticus, might account for the regional differences in breast cancer incidence. In the intervening years, several developments provide additional support for this hypothesis, including the limited impact of genetic factors for breast cancer susceptibility revealed by genome-wide association stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The Authors correlated the high copy numbers of endogenous Mtv in murine species with the potential of generating exogenous, infectious virions by recombination between different Mtvs , as clearly demonstrated in an experimental setting by Golovkina et al [ 128 , 129 ]. In 2004, Levine et al [ 130 ] came to the same conclusion as Stewart et al [ 126 , 127 ] by showing that there was a significantly similar geographic prevalence of MMTVels in humans and MMTV in wild mice. A recent study by Wang et al, in China, found similar evidence, showing that the difference in the prevalence of MMTV-like virus in BC samples from northern (23%) and southern China (6%) could be dependent on the distribution of M. domesticus , M. musculus , and M. castaneus [ 131 ].…”
Section: Mmtv Transmission To Human Species: the Human Mammary Tumor ...mentioning
confidence: 83%
See 4 more Smart Citations
“…The Authors correlated the high copy numbers of endogenous Mtv in murine species with the potential of generating exogenous, infectious virions by recombination between different Mtvs , as clearly demonstrated in an experimental setting by Golovkina et al [ 128 , 129 ]. In 2004, Levine et al [ 130 ] came to the same conclusion as Stewart et al [ 126 , 127 ] by showing that there was a significantly similar geographic prevalence of MMTVels in humans and MMTV in wild mice. A recent study by Wang et al, in China, found similar evidence, showing that the difference in the prevalence of MMTV-like virus in BC samples from northern (23%) and southern China (6%) could be dependent on the distribution of M. domesticus , M. musculus , and M. castaneus [ 131 ].…”
Section: Mmtv Transmission To Human Species: the Human Mammary Tumor ...mentioning
confidence: 83%
“…Several environmental risk factors have been proposed for human sporadic BC, in addition to the presence of MMTV-like sequences. Strikingly, as already discussed, high incidence of human BC has been found to correlate with the predominant presence of a particular mouse strain [ 126 , 127 ]. Based on this correlation, transmission of MMTV from this mouse strain to man was proposed [ 126 , 127 ].…”
Section: Mmtv-like Virus In Companion Animalsmentioning
confidence: 92%
See 3 more Smart Citations